Emergence of Extensively Drug-Resistant Typhoid Fever in Pakistan. - Farhan, Ahmed; Fatima Farooq; Najeeb, Attaina (International Journal of Endorsing Health Science Research, 2024)
Background: Typhoid fever is a significant health concern in Pakistan and Southeast Asia, with Extensively Drug-Resistant (XDR) typhoid fever presenting an escalating public health threat due to increased mortality and morbidity. Recent years have seen two notable XDR typhoid fever epidemics, highlighting the urgent need to investigate this growing problem. This study aims to analyze the prevalence of XDR typhoid fever among patients admitted to our hospital over the past year. Methodology: This retrospective cohort study analyzed data from patients with culture-confirmed typhoid fever admitted to our hospital between July 2022 and June 2023. Patients were divided into two periods based on their illness onset: the first period (July 2022 to December 2022) and the second period (January 2023 to June 2023). Results: A total of 341 patients with culture-confirmed typhoid fever were studied, with 72.7% being male and a mean age of 28.38 ± 7.71 years. The average hospital stay was 12.03 ± 2.79 days, and the mean febrile duration was 6.48 ± 2.3 days. Antibiotic resistance was prevalent, with high resistance rates to ciprofloxacin (78.9%), ampicillin (72.7%), and chloramphenicol (72.7%). Resistance rates significantly increased in the second half of the year, correlating with longer hospital stays and prolonged fever durations for resistant cases. Conclusion: There was a notable increase in the prevalence of XDR typhoid fever within a six-month period. These findings emphasize the need for urgent public health interventions to address the rising threat of XDR typhoid fever.